Influence of limited-creep feeding on pre- and postweaning performance of spring-born calves - C.E. Binns; F.K. Brazle; Gerry L. Kuhl; D.D. Simms; K.O. Zoellner; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1989)
Limit-feeding a high protein creep (36% CP) and a high energy creep (16% CP) was compared with no supplementation in a 61-day preweaning trial. Salt was used to limit daily creep intake to 1.5 to 2.0 lb per head. Calves given the limited energy and protein creep feeds outgained (P<.01) the unsupplemented calves by 0.2 lb and 0.3 lb, respectively. Conversion of creep feed consumed to extra gain was 6.7 and 5.3 for the energy and protein creep-fed calves, respectively (salt included). Trucking shrink of the noncreep-fed calves on the day of weaning and shipping was 4.9 lb and 7.0 lb less (P<.05) than that of the energy and protein creep-fed calves, respectively. Postweaning daily gains of the energy creep-fed calves was higher than those of both the protein creep-fed calves (P=.09) and the noncreep-fed calves (P<.01) by 0.3 lb and 0.5 lb, respectively. The energy creep-fed calves consumed more (P<.05) daily dry matter than the protein creep-fed and unsupplemented calves. Little difference was observed in postweaning feed conversion among creep treatments.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Limited-creep feeding; Performance; Spring calves